Perjanjian Kerjasama Antara Masyarakat Pengelola Wisata Dengan Pemerintah Desa Bonjeruk Kecamatan Jonggat Kabupaten Lombok Tengah - Indah Pratiwi; H. Zaenal Arifin Dilaga; Eka Jaya Subadi (Fakultas Hukum Universitas Mataram, 2023)
This study analyzes 2 problems, namely how to implement the cooperation agreement between the tourism management agency and the Bonjeruk village government, then what are the legal consequences if there is a default in the cooperation agreement between the tourism management agency and the Bonjeruk village government. The type of research used is the normative-empirical legal research method. The legal data approach uses a statute approach, a conceptual approach, and a sociological approach. The results of the study and analysis are that the village government provides financial assistance in cash in the amount of Rp. 78,000,000, - to the managing community in 2020 to develop a tourism business, especially in the Bonjeruk bamboo market. The tourism manager is obliged to pay a sum of money as a contribution to the village government of Rp. 6,000,000 per year for village development. The legal consequence that occurs in the implementation of this agreement is that the agreement does not need to be a lawsuit for null and void the agreement to the judge, but by itself, it is null and void by law, in this case, default is a requirement for cancellation.